Hasil Belajar Calon Guru dalam Perkuliahan Berbasis Proyek: Kajian Deskriptif Pada Mata Kuliah Botani Tumbuhan Tinggi - Yunawati Sele; Ni Putu Yuni Astriani Dewi (BIO-EDU: Jurnal Pendidikan Biologi, 2021)
The purpose of this study was to analyze the learning outcomes of teacher candidates in project-based learning. This research is a descriptive study with a quantitative approach. The research subjects were 26 students of the Biology Education study program at Timor University who were taking the Botany of Higher Plants course. Data was collected using a learning outcome test. The results showed that the learning outcomes of teacher candidates in project-based learning were in a good category with a score of 68.17. This shows that the application of project-based learning has a positive impact on empowering teacher candidates' learning outcomes. Learning becomes not boring and not just memorization because teacher candidates are given the opportunity and responsibility to learn actively from the projects that are carried out. Teacher candidates have a significant role in all stages of project-based learning from project planning, data collection, data organization, data processing, and presentation in project reports. Therefore, it is expected that project-based learning can be done consistently so that it can empower the learning outcomes of teacher candidates.